The Astrolabe by Bulhomal and Pīr Bakhsh of 1841 CE: A Unique Testimonial to an Intercultural Collaboration - Sarma, Sreeramula Rajeswara; Abbasi, Mubashir Ul-Haq (History of Science in South Asia, 2023)
From the middle of the sixteenth century up to the end of the seventeenth, Lahore was the leading centre where Allāhdād and his descendants produced a large number of exquisitely crafted astrolabes, with legends and numerals in Arabic. In the same period, Sanskrit astrolabes with legends in Sanskrit and numerals in Devanagari were made sporadically in Rajasthan-Gujarat region. Then in the eighteenth century, the production of both types of astrolabes ended abruptly for various reasons. Towards the middle of the nineteenth century, however, both these traditions came together in the work of Bulhomal, who created some 27 instruments of diverse kinds.Entirely different from these is a large astrolabe in the creation of which people of different faiths collaborated. The astrolabe was commissioned by Mawlwī Ghulām Muḥammad, a Sunni Muslim, who held an important position at the court of the Sikh rulers of the princely state of Kapurthala, for the sake of Mubārak cAlī Khān who appears to be a member of an influential Shia Muslim family; it was designed by Bulhomal, a Hindu, and was fabricated by Pīr Bakhsh, a Muslim. Thus this astrolabe is a laudable example of intercultural collaboration.The present paper offers a full technical description against the background of Bulhomal’s other work.